Evidence of household consumption changes associated with the global economic slowdown - Florkowski, Wojciech J. (Economics and Business Review, 2012)
The state tracks income changes between two groups of households, i.e., with incomes at or below and above social minimum during the period 2004-2008. The description of spatial variables accounting for differences across voivodships is followed by the description of differences in expenditures on major foods and food categories illustrating the gaps between two household groups over time. The income disparities have been growing during the period under consideration. Low-income households are relatively more dependent on staples and foods that are less desired from a nutritional standpoint. Results suggest the need for intensification of efforts to prevent the poor household segment falling into permanently poor households with possible detrimental effects for overall competitiveness of the national and regional economies. (original abstract)